An adaptive product configurator based on slow intelligence approach. (11th April 2014) - Colace, Francesco; Santo, Massimo De; Greco, Luca
In today's competitive global market, understanding quickly customers' needs is a primary task for a successful design and implementation of customised products. For this aim an effective approach is the adoption of a product configurator. The product configuration is the activity of customising a product to meet the needs of a particular customer that, usually, expresses his/her preferences by the use of the natural language. In this scenario a challenging problem is the definition of a common vocabulary that opens possibilities such as the ability to express the customer requirements and to exchange knowledge. For this aim the adoption of the ontological formalism is an effective approach. Ontology, in fact, is a key factor for enabling interoperability across heterogeneous systems, services and users. This paper presents an ontology–based configurator system that maximally satisfies users' needs starting from the desired requirements, the available components, the context information and previous similar configurations.